A new genus in the family Ptiloneuridae (Psocodea: ‘Psocoptera’: Psocomorpha: Epipsocetae) from Brazil - Da Silva Neto, Alberto Moreira; Aldrete, Alfonso N. García (Zootaxa, 2015)
A new ptiloneurid genus from Brazil, Brasineura n. gen., is described and illustrated. It includes two species, both known only from males, one from the Chapada Diamantina (State of Bahia), and one troglophilic species from the State of Pará. It differs from all other known ptiloneurid genera, in which the males are known, by the unique structure of the phallosome, and by having a uniquely shaped hypandrium of a single sclerite. An updated identification key to the genera of Ptiloneuridae is presented and the synonymy between Brisacia and Loneura is proposed.